Consolidation or multiplicity in supply logistics for health commodities? - Ebenezer Kwabena Tetteh (Elsevier, 2022)
Public health-sectors of most low- and middle-income countries (LMICs) run a central medical stores (CMS) model that is monopolistic in character. Concerns raised about monopolistic CMS arrangements stress the need to encourage cost-reducing efforts and improve service levels (outputs) by having multiple competing logistics institutions. This paper examines the desirability of consolidation or multiplicity in supply logistics by focusing on the task of inventory management (that is, distribution, storage and warehousing). The paper uses theory and historical evidence to describe and suggest a desired form of multiplicity in LMICs. Consolidation shouldn't progress to the point of monopoly and multiplicity doesn't mean having an infinite number of logistics institutions. A limited number (2−10) of logistics institutions, that are full-line and national in their scope and scale of operations, should be enough to provide choice, support competition and minimize the risk of supply disruptions. Health policy and planning in LMICs should explore ways of turning existing logistics institutions in the public, private and non-governmental sectors into a multiplicity of types that are capable of assuring uninterrupted supplies of health commodities.